Pendidikan Karakter Siswa - sudarto sudarto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2016)
The noble design of the Government and our people, which deserves to be supported by all elements. The emergence of awareness applying character education that begins with the phenomenon of degradation of the morality of the young generation today. Due to character education at some schools we have limited discourse so haven't been able to be applied. In such conditions it is difficult to expect improvements to the character of learners. Yet effective character education, it could be due to unpreparedness, and less of understandteachers in him teach.Character education management is the management or arrangement in the field of character education is done through the activities of planning, organizing, controlling, and systematic evaluation. Character education is not just spinning on one region only, for the successful attainment of education character need for the role of families, schools, communities and the many factors that affect the success of character education.Keywords: education, character, students